Food waste separation intention: perspective of university students using S-O-R framework - Ling, Pick-Soon; Ling, Liing-Sing; Phang, Xiao-Yan (2023)
Sustainable behaviour plays an essential role in achieving campus sustainability. A significant concern within university campuses revolves around the excessive food waste, which leads to various environment and social problems. Although food waste separation has been extensively studied in the literature, the evidence from the stimulus-organism-response (S-O-R) perspective and on the university's students remain scarce. Therefore, this study aims to examine the factors that significantly affect university students to separate their food waste using the framework of S-O-R. A total of 214 valid responses were gathered from the university students using purposive sampling, and these responses were further analysed using the partial least squared-structural equation modelling (PLS-SEM). The findings showed that students' attitudes towards food waste separation were significantly influenced by their awareness of consequences, environmental knowledge, and university support. At the same time, the ascription of responsibility was found to have a negligible impact on attitudes. Besides, the study also found that attitudes significantly affect students' intention to separate their food waste. This study provide valuable information that can benefit both literature and stakeholders in this field. Both theoretical and practical implications have been provided and discussed in this study.